Association of combined PD‐L1 expression and tumour‐infiltrating lymphocyte features with survival and treatment outcomes in patients with metastatic melanoma. (24th November 2019) - Bence, C.; Hofman, V.; Chamorey, E.; Long‐Mira, E.; Lassalle, S.; Albertini, A.F.; Liolios, I.; Zahaf, K.; Picard, A.; Montaudié, H.; Lacour, J.P.; Passeron, T.; et al.
Abstract: Background: Recent advances obtained with immune checkpoint inhibitors (ICIs) targeting the programmed cell death‐1 (PD‐1) protein have significantly improved the outcome of patients with metastatic melanoma. The PD‐L1 expression in tumour cells as detected by immunohistochemistry is a predictive biomarker in some solid tumours, but appears insufficient as prognostic or predictive factor of response to ICIs in metastatic melanomas. Objectives: We investigated whether the presence and the features of pretreatment CD8 + tumour‐infiltrating T lymphocytes (TILs) could be a complementary prognostic or predictive biomarker in patients with metastatic melanoma. Methods: In this retrospective study, we evaluated the association of PD‐L1 expression ≥5% of tumour cells combined with TIL features (CD8, CD28, Ki67) with the overall survival (OS) among 51 patients treated with ICIs and 54 patients treated with other treatment options (non‐ICIs). Results: PD‐L1 positivity was observed in 33% and 39% of primary melanomas and matched metastases, respectively, with, however, poor concordance between the primary and the matched metastatic site (κ = 0.283). No significant association was noted between PD‐L1 expression and CD8 + TIL profile analysed as single markers and OS or response to immunotherapy. Instead, their combined analysis in primary melanoma samples showed that the PD‐L1−/CD8 + status was significantly associated with prolonged OS in the whole population ( P  = 0.04) and in the subgroup treated with non‐ICIs ( P  = 0.009). Conversely, the PD‐L1+/CD8 + status was a good prognostic factor in patients treated with ICIs ( P  = 0.022), whereas was significantly associated with poor prognosis in patients treated with non‐ICIs ( P  = 0.014). While the expression of CD28 was not related to outcome, the Ki67 expression was significantly associated with poor OS in the subgroup CD8 + TIL+/PD‐L1− ( P  = 0.02). Conclusions: The pretreatment combination of PD‐L1 expression with the level of CD8 + TILs could better assess OS and predict therapeutic response of patients with metastatic melanoma treated by either immunotherapy or other treatment regimens.